A year in the Maine woods - Heinrich, Bernd, 1940- (Reading, Mass. : Perseus Books, 1994)
"Escapist fantasies usually involve the open road, but Bernd Heinrich's dream was to focus on the riches of one small place--a few green acres along Alder Brook just east of the Presidential Mountains. The year begins as he settles into a cabin with no running water and no electricity, built of hand-cut logs he dragged out of the woods with a team of oxen. There, alone except for his pet raven, Jack, he rediscovers the meaning of peace and quiet and harmony with nature--of days spent not filling out forms, but tracking deer, or listening to the sound of a moth's wings.Throughout this year when "the subtle matters and the spectacular distracts," Heinrich brings us back to the drama in small things, when life is lived consciously. His story is that of a man rediscovering what it means to be alive"--Publisher's website
Keywords: Heinrich, Bernd, -- 1940- -- Homes and haunts -- Maine; Country life -- Maine; Natural history -- Maine; Maine -- Description and travel; Maine -- Description and travel